Bearing Life Calculation and Experimental Evaluation of 6302-2RS Ball Bearing with Grease Lubricant Variations - Wahyu Hidayat; Mohammad Rizal Safri; Rilo Chandra Muhamadin; Ilham Arifin Pahlawan; Alviani Hesthi Permata Ningtyas; Muhammad Arryyanto; Mohammad Rizqi Abdul Basyith (Multidisciplinary Innovations and Research in Applied Engineering, 2026)
Rolling bearings are critical machine elements, but catalogue rating life and short-duration workshop observations must be interpreted separately. This study calculated the ISO 281 basic rating life of a Koyo/JTEKT 6302-2RS deep-groove ball bearing (JTEKT Corp., Kariya, Aichi Japan) and conducted a preliminary comparison of three lubrication treatments. The calculation used the current JTEKT basic dynamic load rating C = 14.3 kN, an equivalent radial load P = 98.1 N, and the ball-bearing exponent p = 3. Three bearings were used (n = 1 per treatment). Their seals were removed, the factory grease was cleaned out, and the specimens were either left without reapplied grease or manually filled with Cobra® Chassis Grease Green No. 3 or Deltalube® 056 General Purpose Grease EP 2; the applied grease mass was not recorded. Each specimen was tested sequentially for 30 min at 1000 rpm and 30 min at 1500 rpm under the same radial load. The corrected basic rating life was 3.097 × 10¹² revolutions, equivalent to 5.162 × 10⁷ h at 1000 rpm and 3.442 × 10⁷ h at 1500 rpm. These very large values reflect an idealized rating-life calculation at a load far below the catalogue capacity and are not an experimentally validated service life. After cumulative testing, the recorded outer-diameter changes were 0.05 mm for the grease-free control, 0.03 mm for Cobra® grease, and 0.01 mm for Deltalube® grease; these changes are comparable with the stated caliper accuracy. At 1500 rpm, the outer-ring radial runout values were 0.30, 0.16, and 0.15 mm, respectively, while the inner-ring values were 0.09, 0.05, and 0.04 mm. Deltalube® grease produced the lowest observed dimensional change and runout under the present conditions, but the unreplicated, sequential test does not support statistical or long-term reliability claims.